The dollar's imperial circle - Ozge Akinci; Gianluca Benigno; Serra Pelin; Jonathan Turek (Federal Reserve Bank of New York, 2022)
In this paper we highlight a new channel through which dollar fluctuations can become a self-fulfilling pro-cyclical force. We call this mechanism "Imperial Circle" as it makes the dollar the dominant macroeconomic variable in the context of the current international monetary system. At the core of it, there is a fundamental asymmetry between the shrinking exposure of the "real" U.S. economy to global developments versus the growing global role of the U.S. dollar. Dollar appreciation leads to a decline in global economic activity, which in turn benefits, in relative terms, the dollar itself, reinforcing the initial appreciation and its effects.
Keywords: E32; E44; F41; 330; multi-country DSGE model; global supply chains; dollar currency pricing; trade spillovers